Supercomputing frontiers and innovations (South Ural State University, 2014)
"Addresses the urgent need for greater dissemination of research and development findings and results at the leading edge of high performance computing systems, highly parallel methods, and extreme scaled applications."
Keywords: Supercomputers : Periodicals; Supercomputers; Computer Science